2005
DOI: 10.1515/jpem.2005.18.11.1111
|View full text |Cite
|
Sign up to set email alerts
|

Depression, Levels of Anxiety and Self-Concept in Girls with Turner's Syndrome

Abstract: Self-esteem, depressive symptoms and anxiety symptoms in girls with Turner's syndrome (TS) were compared to those in girls with familial short stature (FSS) and healthy controls §C).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 8 publications
3
52
1
4
Order By: Relevance
“…They reported that TS girls had significantly lower self-esteem and higher state anxiety levels when compared to control (p<0.05) (Kilic et al, 2005). Another study showed a lower quality of life, higher tension-anxiety scores and impaired cognitive functions in TS girls than agematched controls (Lasaite et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…They reported that TS girls had significantly lower self-esteem and higher state anxiety levels when compared to control (p<0.05) (Kilic et al, 2005). Another study showed a lower quality of life, higher tension-anxiety scores and impaired cognitive functions in TS girls than agematched controls (Lasaite et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…Many studies using parental evaluations and selfreport suggested psychiatric problems in girls and adolescents with TS, in the form of immaturity, diminished social relationships, poor self-concept, depression and social anxiety compared to age-matched controls (Saad et al, 2014;Catinari et al, 2006;McCauley et al, 2001;Kilic et al, 2005;Lasaite et al, 2010;Cardoso et al, 2004). These studies deeply investigated the psychopathological comorbidity in TS patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations